Effects of honeysuckle vine powder on growth, immune performance, and gastrointestinal microbiota structure of Nanjiang Yellow goats - Li, Kerui; Huang, Lian; Zhang, Changhui; Xiang, Hua; Jiang, Kang; Zhao, Wangsheng; Shi, Hengbo; Zhu, Jiangjiang; Du, Zhanyu (Frontiers in Microbiology, 2026)
IntroductionChinese herbal medicines, including honeysuckle (Lonicera japonica), exhibit diverse beneficial properties and are increasingly being explored as feed additives in livestock production to improve animal health and product quality. This study investigates the effects of honeysuckle vine powder (HVP) supplementation as an herbal feed additive on growth performance, immune function, and rumengut microbiota in Nanjiang Yellow goats during fattening.MethodsWe evaluated four dietary groups: control (basal diet) and three experimental groups supplemented with 1% (EG1), 1.5% (EG2), and 2% HVP (EG3) for 60 days. After sampling, we measured the blood biochemical, immune indicators and carried out 16s RNA sequencing of rumen and gut microbiota for Nanjiang Yellow goat samples.ResultsWe evaluated four dietary groups: control (basal diet) and three experimental groups supplemented with 1% (EG1), 1.5% (EG2), and 2% HVP (EG3) for 60 days. Results demonstrated that 2% HVP significantly enhanced, average daily gain (ΔADG = 0.05 ± 0.02 /kg, p < 0.05, n = 8), and feed conversion rate (ΔFCR = 5.26 ± 0.69, p < 0.05, n = 8), while improving body length and chest circumference. Serum immunoglobulin (IgG, IgM) levels were elevated, indicating strengthened systemic immunity (p < 0.05). Critically, 16S rRNA analysis revealed HVP-induced rumen and gut microbiota restructuring, characterized by increased Firmicutes abundance.DiscussionThese findings validate HVP as a sustainable feed additive that optimizes productivity and immune resilience through microbiota-host crosstalk, supporting its application in ecofriendly livestock farming.